The impact of provocative visual stimulation on emotional changes among introverts - Mohd Radzi, Siti Ramizah Khairunnisa; Adzharuddin, Nor Azura; Tamam, Ezhar; Bolong, Jusang (Universiti Putra Malaysia Press, 2019)
Social networking site (SNS) has become a platform for online self-presentation and a replacement of face-to-face (FTF) interaction. Users tend to like or watch the shared video because video sharing is described as a documentary-related meaningful event on SNS. The use of SNS is associated with personality and the site enables users to hide their identity and emotions from others. An Introvert refers to a person with less dominant personality in interaction and socialization. This study aims to explore whether provocative visual sharing in SNS affects emotional changes in Introverts. The experimental study was conducted via online using a post-test group design. A total of 30 Introvert consisting of students aged 20-29 years were selected through purposive sampling. All subjects were added into groups and required to answer a questionnaire before and after watching a provocative visual. Data were analysed using non-parametric test; Mann-Whitney U Test and Wilcoxon-Signed Rank Test. The results shows that there is no emotional differences between gender and insignificance changes in emotion for the Introverts as a whole (z = -1.170, p = 0.077). Their emotion was stable and they did not actively participate in giving comments about the visual. In conclusion, users tend to share a variety of stimulation in SNS but these activities did not affect the Introverts' emotion so much.